A method for preparing 5,5'-diacetyl-2,2'-bifuran
By modifying the alkali metal polycarboxylate on a solid oxide support, enriching palladium ions and carrying out diatom cocatalysis, the problem of limited progress of the biomass-based compound 2-acetylfuran in molecular oxygen oxidation coupling reaction is solved, and efficient preparation of 5,5’-diacetyl-2,2’-cyclofuran is achieved.
Patent Information
- Application Number
- CN202111477344.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-06
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2041-12-06
AI Technical Summary
The prior art is difficult to effectively catalyze the molecular oxygen oxidation coupling reaction of the biomass-based compound 2-acetylfuran, resulting in limited progress of its coupling reaction.
An oxidation coupling catalyst was developed to create an electric field to enrich palladium ions by modifying alkali metal polycarboxylate on a solid oxide support, and diatomic cocatalysis was performed on the support surface using the palladium loading to achieve molecular oxygen oxidation coupling reaction of 2-acetylfuran.
Highly selective conversion of 2-acetylfuran into 5,5'-diacetyl-2,2'-cyclofuran is achieved, and the method is green and efficient, with important application prospects.
Abstract
Description
Technical Field
[0001] The invention relates to the field of preparing chemicals by biomass conversion, and in particular to a method for preparing bifurandione by catalytic conversion of a biomass-based compound 2-acetylfuran under the catalytic action of a catalyst with oxidative coupling action. Background Art
[0002] Biomass is the only renewable organic carbon resource in nature and in the world, and it is widely distributed and abundant in reserves. The preparation of high value-added chemicals from biomass is conducive to reducing the impact of fossil resources on the environment and achieving the goal of carbon neutrality, which is of great significance. Among them, the biomass-based compound 2-acetylfuran not only has an acetyl structure connected to the furan ring, but also has an active 5-position CH bond, which can be converted into a diketone monomer 5,5'-diacetyl-2,2'-bifuran by a stoichiometric palladium oxidative coupling reaction under mild conditions (Synthesis 1984, 1984, 255-256). High-performance degradable polysiloxane materials obtained by chiral catalytic polymerization of diketone monomers and disilanes (ACS Macro Lett. 2020, 9, 969-973). However, the research on the oxidative coupling of 2-acetylfuran by molecular oxygen by catalytic methods has not been reported.
[0003] In recent years, the palladium-catalyzed molecular oxygen oxidation reaction of aromatic CH bonds has received widespread attention. The key step of this reaction is the electrophilic substitution of the aromatic ring by palladium ions. Since the electron-rich aromatic ring substrates have strong nucleophilicity, palladium ions and aromatic rings are prone to electrophilic substitution reactions, and thus the oxidative coupling of electron-rich aromatic rings has made great progress. In contrast, the acetyl group in acetylfuran has a strong electron-withdrawing effect, which weakens the nucleophilicity of the furan ring, and its coupling reaction faces great challenges. To address this issue, we propose to increase the local concentration of palladium ions through catalyst support design, so that two palladium ions can activate two acetylfuran molecules respectively, and then the two generated metal organic species can achieve CC bond coupling of acetylfuran through transmetalation-elimination reaction.
[0004] The object of the present invention is to prepare 5,5'-diacetyl-2,2'-bifuran by catalytic conversion of 2-acetylfuran from biomass. The idea of the present invention is to develop an oxidative coupling catalyst, using oxygen or air as an oxygen source, acetic acid as a solvent, and palladium supported on an oxide carrier modified with polycarboxylate as a catalyst, and 2-acetylfuran undergoes an oxidative coupling reaction to obtain 5,5'-diacetyl-2,2'-bifuran. The method is green, efficient, and has important application prospects. Summary of the invention
[0005] The purpose of the present invention is to develop an efficient oxidative coupling catalyst for preparing low-carbon imprint chemicals using biomass resources as raw materials, alleviating and reducing carbon emissions from fossil resources such as petroleum, and providing new technologies and methods for achieving the goal of carbon neutrality. Specifically, it is to construct a solid oxide carrier modified with alkali metal polycarboxylates, and use the Donnan effect after the dissolution of alkali metal polycarboxylates to construct an electric field on the carrier surface, so that palladium ions are enriched and confined on the carrier surface, and palladium can be freely migrated on the carrier surface, thereby promoting the diatomic palladium co-catalyzed molecular oxygen oxidative coupling reaction of 2-acetylfuran, and preparing 5,5'-diacetyl-2,2'-bifuran with high selectivity.
[0006] According to the method provided by the present invention, the reaction substrate is 2-acetylfuran, which is characterized by containing a ketocarbonyl structure connected to a furan ring in its molecular structure and also having an active 5-position CH bond. It can be obtained from furan by Friedel-Crafts acylation and has great potential application value.
[0007] According to the method provided by the present invention, the solid carrier is: one or more of silica gel, fumed silica, zirconium dioxide, titanium dioxide, aluminum oxide, tungsten trioxide, molybdenum trioxide, and cerium dioxide; preferably one or more of silica gel, zirconium dioxide, titanium dioxide, and aluminum oxide.
[0008] The polyanion is one or more of sodium polystyrene sulfonate, potassium polystyrene sulfonate, sodium lignin sulfonate, lithium polyacrylate, sodium polyacrylate, potassium polyacrylate, cesium polyacrylate, sodium polymaleate, potassium polymaleate, cesium polymaleate, sodium polyitaconate, potassium polyitaconate, cesium polyitaconate, sodium polyepoxysuccinate, potassium polyepoxysuccinate, and cesium polyepoxysuccinate; the molar ratio of metal ions to carboxylic acid groups in the polycarboxylate is 0.1-1; the mass ratio of the polycarboxylate to the solid oxide carrier is 0.1-0.5; preferably one or more of sodium polystyrene sulfonate, sodium polyacrylate, potassium polyacrylate, and cesium polyacrylate.
[0009] The palladium loading is 0.1-10 wt% of the total mass of the catalyst; preferably 0.2-1 wt%.
[0010] The total amount of catalyst is 0.1-5 mol% (Pd / 2-acetylfuran) of the raw material amount of 2-acetylfuran. The reaction temperature is 30-180°C, and the reaction time is 0.1-48h; the preferred reaction temperature is 50-160°C, and the preferred reaction time is 1-20h.
[0011] The oxygen source used in the reaction of the present invention is oxygen or air, and the oxygen partial pressure is 0.1-2MPa.
[0012] According to the route provided by the present invention, the CH bond at position 5 of 2-acetylfuran is oxidatively coupled with molecular oxygen under catalysis to generate 5,5'-diacetyl-2,2'-bifuran in one step.
[0013] According to the method provided by the present invention, the separation and purification methods of the obtained crude product are suction filtration, distillation of the filtrate to remove the solvent, and extraction of the solid matter with water; the solvent used in the extraction process is one or more composite components of ethyl acetate, ether, n-hexane, dichloromethane, etc. After extraction, high-quality 5,5'-diacetyl-2,2'-bifuran is obtained.
[0014] The product was characterized by gas chromatography-mass spectrometry, 1 H NMR analysis was performed and the retention time was compared with that of standard samples.
[0015] The method has a simple catalyst preparation process, high raw material utilization rate, and a target product is obtained with high selectivity. DETAILED DESCRIPTION
[0016] The present invention is described in detail with specific embodiments below, but the implementation of the present invention is not limited to these embodiments:
[0017] The preparation process of the catalyst in the following examples:
[0018] The process of polyanion-modified solid carrier is as follows: the solid carrier and polyanion (the molar ratio of metal ion to carboxylic acid group in polycarboxylate is 0.1-1, and 0.8 is used in the present invention) are physically mixed by ball milling, and then calcined at 100-350°C (300°C used in the present invention) for 1-10h (6h used in the present invention).
[0019] The process of preparing the catalyst is as follows: a polyanion-modified solid carrier is dispersed in one or more of water, ethyl acetate, acetic acid, tetrahydrofuran, dimethyl sulfoxide and dichloromethane (water is used in the present invention), one or more of palladium sulfate, palladium nitrate, palladium chloride and palladium acetate is added, and the mixture is stirred at 20-100° C. (80° C. is used in the present invention) for 1-20 hours (15 hours is used in the present invention), the solvent is dried by spin drying, and the obtained solid is vacuum dried.
[0020] Example 1: 0.5 mmol 2-acetylfuran, 0.2 wt% Pd / lithium polyacrylate-silica gel (the molar ratio of lithium to carboxylic acid group is 0.1, and the mass ratio of lithium polyacrylate to silica gel is 0.1) containing 0.0005 mmol Pd, and 2 mL acetic acid were added to a 20 mL stainless steel reactor with a polytetrafluoroethylene liner, and charged with 0.1 MPa O 2, heated to 100°C, and reacted at this temperature for 12 hours. After the reaction was completed, it was cooled to room temperature, 0.5 mmol of nitrobenzene as internal standard was added, and the volume was diluted to 25 mL for GC analysis. The conversion rate was 70%, and the selectivity of 5,5'-diacetyl-2,2'-bifuran was 65%.
[0021] Example 2: 0.5 mmol 2-acetylfuran, 10 wt% Pd / sodium polyacrylate-fumed silica containing 0.005 mmol Pd (the molar ratio of sodium to carboxylic acid groups is 0.2, and the mass ratio of sodium polyacrylate to fumed silica is 0.2), and 2 mL acetic acid were added to a 20 mL stainless steel reactor with a polytetrafluoroethylene liner, and charged with 0.3 MPa O 2 , heated to 40°C, reacted at this temperature for 0.5h. After the reaction was completed, cooled to room temperature, 0.5mmol nitrobenzene internal standard was added, diluted to 25mL, and used for GC analysis, the conversion rate was 12%, and the selectivity of 5,5'-diacetyl-2,2'-bifuran was 70%.
[0022] Example 3: 0.5 mmol 2-acetylfuran, 3 wt% Pd / potassium polyacrylate-titanium dioxide containing 0.05 mmol Pd (the molar ratio of potassium to carboxylic acid group is 0.3, and the mass ratio of potassium polyacrylate to titanium dioxide is 0.3), and 2 mL acetic acid were added to a 20 mL stainless steel reactor with a polytetrafluoroethylene liner, and charged with 0.12 MPa O 2 , heated to 30°C, and reacted at this temperature for 48 hours. After the reaction was completed, the mixture was cooled to room temperature, 0.5 mmol of nitrobenzene as internal standard was added, and the volume was diluted to 25 mL for GC analysis. The conversion rate was 59%, and the selectivity of 5,5'-diacetyl-2,2'-bifuran was 61%.
[0023] Example 4: 0.5 mmol 2-acetylfuran, 4 wt% Pd / cesium polyacrylate-zirconium dioxide containing 0.001 mmol Pd (the molar ratio of cesium to carboxylic acid group is 0.4, and the mass ratio of cesium polyacrylate to zirconium dioxide is 0.4), and 2 mL acetic acid were added to a 20 mL stainless steel reactor with a polytetrafluoroethylene liner, and charged with 0.14 MPa O 2 , heated to 50°C, and reacted at this temperature for 33 hours. After the reaction was completed, it was cooled to room temperature, 0.5 mmol of nitrobenzene as internal standard was added, and the volume was diluted to 25 mL for GC analysis. The conversion rate was 58%, and the selectivity of 5,5'-diacetyl-2,2'-bifuran was 55%.
[0024] Example 5: 0.5 mmol 2-acetylfuran, 0.6 wt% Pd / polysodium maleate-aluminum oxide (the molar ratio of sodium to carboxylic acid group is 0.5, the mass ratio of polysodium maleate to aluminum oxide is 0.5) containing 0.002 mmol Pd, and 2 mL acetic acid were added to a 20 mL stainless steel reactor lined with polytetrafluoroethylene, and charged with 0.16 MPa O 2 , heated to 60°C, and reacted at this temperature for 24 hours. After the reaction was completed, the mixture was cooled to room temperature, 0.5 mmol of nitrobenzene as internal standard was added, and the volume was diluted to 25 mL for GC analysis. The conversion rate was 81%, and the selectivity of 5,5'-diacetyl-2,2'-bifuran was 63%.
[0025] Example 6: 0.5 mmol 2-acetylfuran, 0.8 wt% Pd / polypotassium maleate-tungsten trioxide (the molar ratio of potassium to carboxylic acid group is 0.6, and the mass ratio of polypotassium maleate to tungsten trioxide is 0.4) containing 0.003 mmol Pd, and 2 mL acetic acid were added to a 20 mL stainless steel reactor lined with polytetrafluoroethylene, and charged with 0.18 MPa O 2 , heated to 80°C, and reacted at this temperature for 12 hours. After the reaction was completed, the mixture was cooled to room temperature, 0.5 mmol of nitrobenzene as internal standard was added, and the volume was diluted to 25 mL for GC analysis. The conversion rate was >99%, and the selectivity of 5,5'-diacetyl-2,2'-bifuran was 79%.
[0026] Example 7: 0.5 mmol 2-acetylfuran, 1 wt% Pd / polycesium maleate-molybdenum trioxide (the molar ratio of cesium to carboxylic acid group is 0.7, and the mass ratio of polycesium maleate to molybdenum trioxide is 0.3) containing 0.005 mmol Pd, and 2 mL acetic acid were added to a 20 mL stainless steel reactor with a polytetrafluoroethylene liner, and charged with 0.1 MPa O 2 , heated to 90°C, and reacted at this temperature for 21 hours. After the reaction was completed, it was cooled to room temperature, 0.5 mmol of nitrobenzene as internal standard was added, and the volume was diluted to 25 mL for GC analysis. The conversion rate was 85%, and the selectivity of 5,5'-diacetyl-2,2'-bifuran was 60%.
[0027] Example 8: 0.5 mmol 2-acetylfuran, 1 wt% Pd / sodium polyitaconate-cerium dioxide (the molar ratio of sodium to carboxylic acid group is 0.8, the mass ratio of sodium polyitaconate to cerium dioxide is 0.2) containing 0.005 mmol Pd, and 2 mL acetic acid were added to a 20 mL stainless steel reactor with a polytetrafluoroethylene liner, and charged with 0.1 MPa O 2, heated to 100°C, and reacted at this temperature for 15 hours. After the reaction was completed, it was cooled to room temperature, 0.5 mmol of nitrobenzene as internal standard was added, and the volume was diluted to 25 mL for GC analysis. The conversion rate was 89%, and the selectivity of 5,5'-diacetyl-2,2'-bifuran was 59%.
[0028] Example 9: 0.5 mmol 2-acetylfuran, 2 wt% Pd / potassium polyitaconate-cerium dioxide (the molar ratio of potassium to carboxylic acid group is 0.9, the mass ratio of potassium polyitaconate to cerium dioxide is 0.1) containing 0.005 mmol Pd, and 2 mL acetic acid were added to a 20 mL stainless steel reactor lined with polytetrafluoroethylene, and charged with 0.2 MPa O 2 , heated to 120°C, and reacted at this temperature for 16 hours. After the reaction was completed, it was cooled to room temperature, 0.5 mmol of nitrobenzene as internal standard was added, and the volume was diluted to 25 mL for GC analysis. The conversion rate was >99%, and the selectivity of 5,5'-diacetyl-2,2'-bifuran was 54%.
[0029] Example 10: 0.5 mmol 2-acetylfuran, 0.5 wt% Pd / potassium polyitaconate-titanium dioxide (the molar ratio of potassium to carboxylic acid group is 1, and the mass ratio of potassium polyitaconate to titanium dioxide is 0.5) containing 0.005 mmol Pd, and 2 mL acetic acid were added to a 20 mL stainless steel reactor lined with polytetrafluoroethylene, and charged with 1.3 MPa O 2 , heated to 140°C, and reacted at this temperature for 5 hours. After the reaction was completed, it was cooled to room temperature, 0.5 mmol of nitrobenzene as internal standard was added, and the volume was diluted to 25 mL for GC analysis. The conversion rate was >99%, and the selectivity of 5,5'-diacetyl-2,2'-bifuran was 85%.
[0030] Example 11: 0.5 mmol 2-acetylfuran, 0.8 wt% Pd / lithium polyepoxysuccinate-zirconium dioxide (the molar ratio of lithium to carboxylic acid group is 0.9, the mass ratio of lithium polyepoxysuccinate to zirconium dioxide is 0.1) containing 0.005 mmol Pd, and 2 mL acetic acid were added to a 20 mL stainless steel reactor with a polytetrafluoroethylene liner, and charged with 1.5 MPa O 2 , heated to 130°C, and reacted at this temperature for 4 hours. After the reaction was completed, it was cooled to room temperature, 0.5 mmol of nitrobenzene as internal standard was added, and the volume was diluted to 25 mL for GC analysis. The conversion rate was >99%, and the selectivity of 5,5'-diacetyl-2,2'-bifuran was 87%.
[0031] Example 12: 0.5 mmol 2-acetylfuran, 6 wt% Pd / sodium polyepoxysuccinate-tungsten trioxide (the molar ratio of sodium to carboxylic acid group is 0.9, and the mass ratio of sodium polyepoxysuccinate to tungsten trioxide is 0.1) containing 0.005 mmol Pd, and 2 mL acetic acid were added to a 20 mL stainless steel reactor with a polytetrafluoroethylene liner, and charged with 2.0 MPa O 2 , heated to 150°C, reacted at this temperature for 0.5h. After the reaction was completed, cooled to room temperature, 0.5mmol nitrobenzene internal standard was added, diluted to 25mL, and used for GC analysis, the conversion rate was 77%, and the selectivity of 5,5'-diacetyl-2,2'-bifuran was 74%.
[0032] Example 13: 0.5 mmol 2-acetylfuran, 0.6 wt% Pd / polyepoxy potassium succinate-zirconium dioxide containing 0.025 mmol Pd (the molar ratio of potassium to carboxylic acid group is 1, and the mass ratio of polyepoxy potassium succinate to zirconium dioxide is 0.3), and 2 mL acetic acid were added to a 20 mL stainless steel reactor with a polytetrafluoroethylene liner, and charged with 0.12 MPa O 2 , heated to 160°C, reacted at this temperature for 0.2h. After the reaction was completed, cooled to room temperature, 0.5mmol nitrobenzene internal standard was added, diluted to 25mL, and used for GC analysis. The conversion rate was >99%, and the selectivity of 5,5'-diacetyl-2,2'-bifuran was 86%.
[0033] Example 14: 0.5 mmol 2-acetylfuran, 3 wt% Pd / sodium polystyrene sulfonate-zirconium dioxide (the molar ratio of sodium to sulfonic acid group is 1, the mass ratio of sodium polystyrene sulfonate to zirconium dioxide is 0.2) containing 0.025 mmol Pd, and 2 mL acetic acid were added to a 20 mL stainless steel reactor with a polytetrafluoroethylene liner, and charged with 0.12 MPa O 2 , heated to 160°C, reacted at this temperature for 0.2h. After the reaction was completed, cooled to room temperature, 0.5mmol nitrobenzene internal standard was added, diluted to 25mL, and used for GC analysis. The conversion rate was >89%, and the selectivity of 5,5'-diacetyl-2,2'-bifuran was 46%.
[0034] Example 15: 0.5 mmol 2-acetylfuran, 1 wt% Pd / polystyrene sulfonate potassium-titanium dioxide (the molar ratio of sodium to sulfonic acid group is 0.6, the mass ratio of polystyrene sulfonate sodium to zirconium dioxide is 0.4) containing 0.005 mmol Pd, and 2 mL acetic acid were added to a 20 mL stainless steel reactor with a polytetrafluoroethylene liner, and charged with 0.12 MPa O 2, heated to 160°C, reacted at this temperature for 0.2h. After the reaction was completed, cooled to room temperature, 0.5mmol nitrobenzene internal standard was added, diluted to 25mL, and used for GC analysis. The conversion rate was >87%, and the selectivity of 5,5'-diacetyl-2,2'-bifuran was 86%.
[0035] Example 16: 0.5 mmol 2-acetylfuran, 1 wt% Pd / cesium polystyrene sulfonate-titanium dioxide containing 0.01 mmol Pd (the molar ratio of cesium to sulfonic acid group is 0.9, and the mass ratio of cesium polystyrene sulfonate to zirconium dioxide is 0.3), and 2 mL acetic acid were added to a 20 mL stainless steel reactor with a polytetrafluoroethylene liner, and charged with 0.12 MPa O 2 , heated to 160°C, and reacted at this temperature for 0.2h. After the reaction was completed, cooled to room temperature, 0.5mmol of nitrobenzene as internal standard was added, and the volume was diluted to 25mL for GC analysis. The conversion rate was >49%, and the selectivity of 5,5'-diacetyl-2,2'-bifuran was 46%.
[0036] Comparative Example:
[0037] Comparative Example 1: 0.5 mmol 2-acetylfuran, 0.2 wt% Pd / silica gel containing 0.0005 mmol Pd, and 2 mL acetic acid were added to a 20 mL stainless steel reactor with a polytetrafluoroethylene liner and filled with 0.1 MPa O 2 , heated to 100°C, and reacted at this temperature for 12 hours. After the reaction was completed, it was cooled to room temperature, 0.5 mmol of nitrobenzene as internal standard was added, and the volume was diluted to 25 mL for GC analysis. The conversion rate was 91%, and the selectivity of 5,5'-diacetyl-2,2'-bifuran was <1%.
[0038] Comparative Example 2: 0.5 mmol 2-acetylfuran, 2 wt% Pd / lithium polyacrylate containing 0.0005 mmol Pd, and 2 mL acetic acid were added to a 20 mL stainless steel reactor lined with polytetrafluoroethylene, and charged with 0.1 MPa O 2 , heated to 100°C, and reacted at this temperature for 12 hours. After the reaction was completed, it was cooled to room temperature, 0.5 mmol of nitrobenzene as internal standard was added, and the volume was diluted to 25 mL for GC analysis. The conversion rate was 40%, and the selectivity of 5,5'-diacetyl-2,2'-bifuran was 33%.
[0039] The present invention develops a highly efficient oxidative coupling catalyst, using the biomass-based derivative 2-acetylfuran as raw material, acetic acid as reaction medium, and oxygen or air as oxygen source, to produce 5,5'-diacetyl-2,2'-bifuran under catalytic action. This technical route is of great significance for alleviating the shortage of petroleum resources and achieving the goal of carbon neutrality.
Claims
1. A method for preparing 5,5'-diacetyl-2,2'-bifuran, characterized in that: Using oxygen and / or air as an oxygen source, acetic acid as a solvent, and palladium supported on a polyanion-modified solid carrier as a catalyst, 2-acetylfuran undergoes an oxidative coupling reaction to obtain 5,5'-diacetyl-2,2'-bifuran; The solid carrier is one or more of silica gel, fumed silica, zirconium dioxide, titanium dioxide, aluminum oxide, tungsten trioxide, molybdenum trioxide, and cerium dioxide; The polyanion is one or more of sodium polystyrene sulfonate, potassium polystyrene sulfonate, sodium lignin sulfonate, lithium polyacrylate, sodium polyacrylate, potassium polyacrylate, cesium polyacrylate, sodium polymaleate, potassium polymaleate, cesium polymaleate, sodium polyitaconate, potassium polyitaconate, cesium polyitaconate, sodium polyepoxysuccinate, potassium polyepoxysuccinate, and cesium polyepoxysuccinate; the molar ratio of metal ions to carboxylic acid groups in the polycarboxylate is 0.1-1; and the mass ratio of the polycarboxylate to the solid oxide carrier is 0.1-0.
5.
2. The method according to claim 1, characterized in that: The palladium loading is 0.1-10wt% of the total mass of the catalyst.
3. The method according to claim 2, characterized in that: The palladium loading is 0.2-1 wt% of the total mass of the catalyst.
4. The method according to claim 1, characterized in that: The total amount of catalyst used is 0.1-5 mol% Pd / 2-acetylfuran based on the amount of 2-acetylfuran used.
5. The method according to claim 4, characterized in that: The total amount of catalyst used is 0.2-2 mol% Pd / 2-acetylfuran based on the amount of 2-acetylfuran used.
6. The method according to claim 5, characterized in that: The total amount of catalyst used is 0.2-1 mol% Pd / 2-acetylfuran based on the amount of 2-acetylfuran used.
7. The method according to claim 1, characterized in that: Oxygen or air or both are used as oxygen sources, and the oxygen partial pressure is 0.1-2 MPa.
8. The method according to claim 7, characterized in that: Oxygen or air or both are used as oxygen sources, and the oxygen partial pressure is 0.5-1.5 MPa.
9. The method according to claim 8, characterized in that: Oxygen or air or both are used as oxygen sources, and the oxygen partial pressure is 0.8-1.5 MPa.
10. The method according to claim 1, characterized in that: The reaction temperature for the catalytic conversion of 2-acetylfuran is 30-180 o C, reaction time is 0.1-48 h.
11. The method according to claim 1, characterized in that: The process of modifying the solid support with polyanion is as follows: the solid support and the polyanion are physically mixed by ball milling, 100-350 o C calcination for 1-10 h.
12. The method according to claim 1, characterized in that: The preparation process of the catalyst is as follows: a solid carrier modified with a polyanion is dispersed in one or more of water, ethyl acetate, acetic acid, tetrahydrofuran, dimethyl sulfoxide, and dichloromethane, and one or more of palladium sulfate, palladium nitrate, palladium chloride, and palladium acetate are added. o After stirring at 400 °C for 1-20 h, the solvent was evaporated and the obtained solid was dried in vacuo.
Citation Information
Patent Citations
Novel method for preparing 5, 5 '-dialkyl-2, 2'-bifuran compound from 2-alkyl furan
CN111848555A
Method for Aerobic Oxidative Coupling of Thiophenes with a Ligand-Supported Palladium Catalyst
US20190210993A1